Hogarth's legacy - Roman, Cynthia E. (Miscellaneous antiquities, 2016)
"The legacy of graphic artist William Hogarth (1697-1764) remains so emphatic that even his last name has evolved into a common vernacular term referring to his characteristically scathing form of satire. Featuring rarely seen images and written contributions from leading scholars, this book showcases a collection of the artist's works gathered from the Lewis Walpole Library at Yale University and other repositories. It attests to the idiosyncratic nature of his style and its international influence, which continues to incite aesthetic and moral debate among critics. The eight essays by eminent Hogarth experts help to further contextualize the artist's unique narrative strategies, embedding the work within German philosophical debates and the moral confusion of the Victorian period and emphasizing the social and political dimensions that are part and parcel of its profound impact. Endlessly parodied and emulated, Hogarth's distinctive satire persists in its influence throughout the centuries and this publication provides the necessary lens through which to view it. "--